2006
DOI: 10.1038/sj.leu.2404212
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a novel zinc finger protein (HZF1) gene and its function in erythroid and megakaryocytic differentiation of K562 cells

Abstract: A novel zinc finger protein (HZF1) gene was identified and characterized by screening a human bone marrow cDNA library, using a new expression sequence tag probe that contains sequences encoding zinc finger motifs. There are at least three transcripts that may result from different splicing of the pre-mRNA, but the differences among them are only involved in 5 0 non-translation region of HZF1 mRNA. HZF1 gene contains four exons and three introns. The putative protein consists of 670 amino-acid residues includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 25 publications
0
20
0
1
Order By: Relevance
“…Primary antibody against HZF1 was raised in rabbit as previously described (7). Additional primary antibodies used for immunoprecipitation or Western blot analysis detection were rabbit polyclonal-pRb (Abcam, UK), mouse monoclonal-Rb (Abcam), mouse monoclonal-c-Myc (Santa Cruz), mouse monoclonal-Flag (Santa Cruz) and mouse monoclonal-GAPDH (Clontech).…”
Section: Co-immunoprecipitation and Western Blot Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…Primary antibody against HZF1 was raised in rabbit as previously described (7). Additional primary antibodies used for immunoprecipitation or Western blot analysis detection were rabbit polyclonal-pRb (Abcam, UK), mouse monoclonal-Rb (Abcam), mouse monoclonal-c-Myc (Santa Cruz), mouse monoclonal-Flag (Santa Cruz) and mouse monoclonal-GAPDH (Clontech).…”
Section: Co-immunoprecipitation and Western Blot Analysismentioning
confidence: 99%
“…By using an antisense method and a RNA inference assay, we previously showed that repression of the intrinsic expression of HZF1 reduced hemin-induced erythroid differentiation and phorbol myristate acetate (PMA)-induced megakaryocytic differentiation of K562 cells, suggesting its significant role in erythroid and megakaryocytic differentiation (7). The Northern blot assay revealed that HZF1 was extensively expressed in human tissues and cell lines (7), indicating that HZF1 may be involved in the regulation of certain significant cellular functions. In this study, HZF1 overexpression was found to accelerate the proliferation of K562 cells by facilitating the cell cycle phase transition from the S to G2/M phase, and slightly inhibited the apoptosis of K562 cells.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations